(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes the microcosm - a system of cells and molecules - in human blood from a histological and biophysical point of view. The possibility of identifying such pathological conditions as inflammation, anemia, thrombosis, immune and oncological processes by means of changes in the blood are considered.